EQUATIONS OF STATE OF AL, AU, CU, PT, TA, AND W AND REVISED RUBY PRESSURE SCALE - Dorogokupets P.I.; Oganov A.R. (My University, 2006)
The ruby pressure scale, in which pressure is measured on the basis of the R1 line shift of ruby luminescence, has been reconsidered. The wellknown ruby scale, which was calibrated using room-temperature isotherms of Cu and Ag reduced from shock-wave data, has been significantly shifted towards the ruby pressure scale, based on an a priori equation of state of diamond. Various functional dependences of pressure on the R1 line shift of ruby luminescence have been proposed.